Modification of PTFE flat sheet film via radiation induced grafting polymerization with acrylic acid - Faezeah Abd Ghani,; Khaidzir Hamzah,; Nor Hasimah Mohamed, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Polytetrafluoroethylene (PTFE) flat sheet film was modified with acrylic acid (AAC) by radiation induced grafting polymerization (RIGP) method using electron beam. The adsorbed doses were varied from 10 to 50 kGy, time of grafting from 1 to 3 h and monomer concentration and temperature were kept constant at 30 wt. % and 40ºC. The degree of grafting (Dg) and equilibrium degree of swelling (EDS) of the grafted films were then determined. The films were further characterized by Fourier transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), atomic force microscope (AFM), X-ray diffraction (XRD), and optical water contact angle. Dg within the range of 17% to 210% were obtained for doses from 10 to 50 kGy within time of grafting from 1 to 3 h. The grafted film (PTFE-g-AAC) showed increased hydrophilicity leading to an increase in EDS. The successful grafting process was confirmed by FTIR results that showed characteristics peaks for carbonyl and hydroxyl group and a decrease in crystallinity for the PTFE-g-AACfilm. SEM images showed that PTFE-g-AAC films had less fibrillar compared to PTFE film and was consistent with the decrease in roughness for the PTFE-g-AAC film. This study indicated that modifying PTFE film by grafting AAC could significantly improve the hydrophilicity of PTFE film. The PTFE-g-AAC films has potential as a heavy metal adsorbent as it can remove at least 75% of Fe ion and 50 % of Pb ion from competitive media.